(untitled) (Heritage, 2026)
Self-translation represents a specific form of translation practice in which the roles of author and translator overlap, raising questions of authorial freedom, interpretation, and cultural mediation. In contemporary translation studies, self-translation is increasingly viewed through translingual and cultural approaches that emphasize the dynamic relationship between language, culture, and identity. This paper explores the cultural aspects of self-translation through an analysis of selected works by Lana Bastašić and Vesna Goldsworthy. Based on a contrastive analysis of original texts and their self-translations, the paper examines how these authors approach culturally marked elements, as well as the strategies they employ in adapting the text to a new linguistic and cultural context. The analysis demonstrates that in both cases, self-translation functions as a creative and interpretative process, where the self-translation constitutes an equal part of the author’s body of work. ​